2008
DOI: 10.1007/bf03175553
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the cyanobacteriaAnabaena wisconsinense andOscillatoria curviceps against pathogens of fish in aquaculture

Abstract: Cultures of the blue green algae (cyanobacteria) Anabaena wisconsinense and Oscillatoria curviceps were isolated from fish farms and their antimicrobial effects were studied. Solvent extracts of exponential phase algae were screened for antimicrobial activity against different species of Gram positive (Lactobacillus sp. and Bacillus firmus) and Gram negative (Aeromonas hydrophila, Pseudomonas fluorescens and Pseudomonas anguilliseptica) bacteria and the fungi (Aspergillus niger and Saprolegnia parasitica) whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A polyphasic study recently published by Saber et al (2017) on this cyanobacterial species unveiled an array of low unsaturated and short fatty acyl chains, typically C16 and C18, which possibly played a role in the antimicrobial effect observed here. The antimicrobial activities of the fatty acids extracted from cyanobacteria, and also seaweeds (e.g., Mohamed & Saber, 2019 and the references therein), have already been discussed in several previous studies (e.g., Soltani et al, 2005;El-Sheekh et al, 2008 and the references therein). The mode of action of these antimicrobial substances is basically different from the metabolite per se.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…A polyphasic study recently published by Saber et al (2017) on this cyanobacterial species unveiled an array of low unsaturated and short fatty acyl chains, typically C16 and C18, which possibly played a role in the antimicrobial effect observed here. The antimicrobial activities of the fatty acids extracted from cyanobacteria, and also seaweeds (e.g., Mohamed & Saber, 2019 and the references therein), have already been discussed in several previous studies (e.g., Soltani et al, 2005;El-Sheekh et al, 2008 and the references therein). The mode of action of these antimicrobial substances is basically different from the metabolite per se.…”
Section: Discussionmentioning
confidence: 85%
“…The rapid growth of resistance in pathogenic bacteria and fungi has recently led to the necessity for a new strategy in drug development by depending on antimicrobial products of natural origin (e.g., El-Sheekh et al, 2008;Righini & Roberti, 2019;Besednova et al, 2020). Members of the phylum Cyanobacteria, in particular the heterocytous genera and taxa, have been characterized as keystone producers of biologically active and structurally diverse compounds with high-value pharmaceutical importance (El-Sheekh et al, 2008;Saurav et al, 2019;Khalifa et al, 2021). However, our understanding of the antimicrobial potential of the dryland-inhabiting taxa, such as the poorly studied Westiellopsis prolifica (Hapalosiphonaceae, Nostocales), remains scarce in this area of research.…”
Section: Introductionmentioning
confidence: 99%
“…So, a large abundance of harmful cyanobacteria in pond T3 may be the reason for the difference. A pervious study reported that solvent extracts of harmful cyanobacteria ( Anabaena wisconsinense and Oscillatoria curviceps ) had antimicrobial effects on various microbes (El‐Sheekh, Dawah, Abd El‐Rahman, El‐Adel & El‐Hay Abd ). Species of Oscillatoria usually can produce microcystins (van Apeldoorn, van Egmond, Speijers & Bakker ), and these cyanotoxins also may affect the water bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC result of zataria essence against Saprolegnia was 0.9 and against fusarium was 1.4 ppm [18]. In the study of El-Sheekh (2008), methanol extracts of Anabaena wisconsinense and Oscillatoria curviceps had antifungal effects against A.niger and Saprolegnia parasitica [19]. In the study by Endler et al (2008), they reported that the accumulation of alkaloids and coumarins but not flavonoids was enhanced in Ruta graveolens suspension cultures upon the addition of fungal elicitor [20].…”
Section: Discussionmentioning
confidence: 99%